Hermeneutic Existential Phenomenology as a psychotherapeutic and philosophical attunement to educate novice researchers - Segal, Steven (European Journal for Qualitative Research in Psychotherapy, 2024)
This paper develops a hermeneutic existential phenomenological (HEP) approach to the research education of novice researchers. Drawing from HEP in psychotherapy and philosophy leads to the identification of the importance of lived experience in educating novice researchers. It demonstrates the significance of responding effectively to existential struggles for embodying and inhabiting the way of being of research with competence and confidence. HEP provides a framework for turning the messiness and chaos of the lived experience of research into opportunities for research education and development. Creating the space for turning the emotional “roller coaster” ride of research into educational opportunities requires the skills of a psychotherapist who enables the novice researcher to stay with and learn to listen to their research doubts and anxieties. These skills are also formulated by existential philosophers who write about being resolute in moments of vulnerability and anxiety. A HEP approach to research education is a contribution that psychotherapy and philosophy have to offer research education in psychotherapy and in general. Working educationally with the existential anxiety of research is useful in any research area that acknowledges the importance of being attuned to lived experience in the process of becoming a researcher.